Fotografia e memória autobiográfica no Facebook: narrativas de si mediadas pela imagem - Carneiro, Jéssica de Souza (2016)
The study of memory and narrative and its relation with the production and consumption of images has shown a challenging course, especially nowadays, when we try to understand these processes in digital environments. The photo operates in the processes of meaning attribution, that is, the meanings that subjects give to a certain event, in how people and events are remembered, narrated and understood. In particular, the digital photograph produced in order to be shared online introduces an interesting field of research of both and autobiographical memory and narration. This study proposes to analyze the photos shared on Facebook that play on the autobiographical memories, with effect therefore on current forms of self-narration. In other words, we try to understand how the new digital ways of producing images (especially those produced to be shared) operate in the way users build their memories of a lived moment, articulating the past, present and future from the mediatized images. In addition, we investigate how these new ways of "saving" memory influence the creation of current autobiographical narratives, that is, the stories that people tell about themselves. The qualitative study consisted in two stages: 1) application of semi-structured questionnaire with topics about photography and memory; 2) coding and analysis of the photographs available for research, selected by respondents. The invitation to participate was given on Facebook. We identified the factors that contributed to the process of choosing the shared images, as well as the individual and social processes that circumscribe the practices of production of digital photography sharing, with the intention of establishing a relationship between the production of memory and self-narratives.